Mechanical, histological and histomorphometric evaluation of modified by femtosecond laser zirconia implants versus titanium implants. An experimental study in dogs at three months - J.L. Calvo-Guirado; C. Perez-Albacete Martínez; B. Negri; R.A. Delgado-Ruíz; P. Ramirez-Fernández; J.E. Mate-Sánchez; M. Abooud; J. Gargallo Albiol; M. Satorres Nieto (Ariesdue, 2013)
Aim The present study was aimed at quantifying implant´s stability and elemental composition by Periotest® and evaluating bone to implant contact (BIC) and crestal bone loss of modified by femtosecond laser zirconia and titanium implants.Materials and methods Forty-eight implants were divided into 2 groups: titanium (control) and modified by femtosecond laser zirconia (test) and then inserted in 6 American Foxhound dogs. Primary stability and secondary stability were measured by Periotest, BIC was evaluated by histomorphometry at 1 and 3 months, elemental composition of the surrounding bone in both groups after 1 and 3 months was assessed.Results Differences between groups regarding primary stability and secondary stability were not significant (p>0.05). The Carbon ratio at zirconia (12.529%) was significantly lower (p<0.05) at 1 month than titanium (15.776%). The highest Calcium rates were found on titanium (16.248% and 17.007%), but the differences between groups were not significant. No statistically significant differences (p>0.05) regarding BIC for titanium vs modified zirconia were observed. Crestal bone loss at 3 months was significantly (p<0.05) lower (0.07 ±0.34 mm) in titanium group than in zirconia (1.25 ± 1.73 mm).Conclusion Surface treatment by using femtosecond laser equalizes osseointegration of zirconia implants.